2022
DOI: 10.1155/2022/9557859
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA TUG1 Inhibits Tumor Progression through Regulating Siglec-15-Related Anti-Immune Activity in Hepatocellular Carcinoma

Abstract: Background. Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death, and its biology remains poorly understood, especially in regards to the immunosuppression induced by immune checkpoints, such as Siglec-15. Most cancer treatments composed of immune checkpoint inhibitors and oncogene-targeted drugs display a better therapeutic effect in the clinic, including tumor progression inhibition and immunosuppression breaks. However, two or more drugs will result in a greater possibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In recent years, some studies have found that Siglec-15 is involved in the progression of various tumors [ 10 , 27 , 28 ]. At present, there are few studies on this aspect of osteosarcoma, and a previous study showed that Siglec-15 is involved in the invasion and migration of osteosarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have found that Siglec-15 is involved in the progression of various tumors [ 10 , 27 , 28 ]. At present, there are few studies on this aspect of osteosarcoma, and a previous study showed that Siglec-15 is involved in the invasion and migration of osteosarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a three-gene prognostic model associated with immunity that was constructed using TCGA datasets to predict the OS outcomes of patients with LKB1 -mutant LUAD. These same three genes have been identified as prognostic biomarkers in multiple tumor types, and have been found to play important roles in the occurrence and development of various diseases by regulating immune function ( Moschovaki Filippidou et al, 2020 ; Zhang et al, 2020 ; Hu et al, 2021 ; Ren et al, 2022 ). The AUC values of ROC curves suggested that our risk model had a superior prognostic value to other clinicopathological characteristics, including age, gender, and stage.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA TUG1 underlined a tumor promotive property via impairing miR-421-mediated suppression of KDM2A and activating the ERK signaling in colorectal cancer cells ( 62 ). TUG1 suppressed cancer progression via targeting Siglec-15-mediated anti-immune activity in HCC ( 63 ). Moreover, TUG1 was reported to sponge miR-328-3p and increase the SRSF9 mRNA expression in HCC cells, leading to promotion of proliferation, invasion and migration ( 64 ).…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%